Effect of the COVID-19 Pandemic and Other Predictors of True Therapeutic Inertia on Patients with Hypertension in a Primary Care Clinic in Thailand - Sornsenee P; Vichitkunakorn P; Choomalee K; Romyasamit C (Dove Medical Press, 2021)
Phoomjai Sornsenee, 1 Polathep Vichitkunakorn, 1 Kittisakdi Choomalee, 1 Chonticha Romyasamit 2 1Department of Family and Preventive Medicine, Faculty of Medicine, Prince of Songkla University, Songkhla, Thailand; 2Department of Medical Technology, School of Allied Health Sciences, Walailak University, Nakhon Si Thammarat, ThailandCorrespondence: Phoomjai Sornsenee Tel +66954204713Email ezipnary@gmail.comIntroduction: Hypertension (HT) has a significant impact on health care worldwide. Therapeutic inertia (TI) is defined as the failure to intensify therapy in the absence of an optimal goal and is widely used as a quality of care parameter. The coronavirus disease 2019 (COVID-19) pandemic has affected many health-care systems, including HT care. Therefore, the present study assessed the impact of the COVID-19 pandemic on TI and its predictors in patients with HT.Methods: The electronic medical records of patients with HT who attended a primary care clinic at a tertiary hospital during pre-COVID-19 (February 2019 to February 2020) and COVID-19 (March to August 2020) periods were reviewed.Results: Our study included 6089 visits during the 12-month pre-COVID-19 period and 2852 visits during the 6-month COVID-19 period. Most of the baseline characteristics of the HT patients were not significantly different between the two time periods. During the COVID-19 period, the percentage of uncontrolled HT visits decreased from 43% to 31%. Similarly, the prevalence of TI decreased from 81% to 77%. False TI was predominantly due to physicians’ concerns regarding the in-clinic blood pressure measurement being inaccurate during both the periods.Conclusion: After readjustment for the physicians ‘reasons, the true TI was 64% and 60% in the pre-COVID-19 and COVID-19 period. For adjusted physician and patient-related factors, multilevel modeling was used. Senior medical staff visits, elderly patients, prior diabetes mellitus diagnosis, patients who used more than one type of anti-HT medication, and patients with systolic blood pressure > 150 mmHg were all predictors of TI. The COVID-19 period, on the other hand had no effect on TI with an adjusted odds ratio of 0.82 (95% confidence interval, 0.67– 1.01).Keywords: hypertension, therapeutic inertia, COVID-19, quality of care, multilevel modeling, primary care